2020
DOI: 10.7759/cureus.10480
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Options for COVID-19: A Review

Abstract: An acute respiratory disease caused by a novel coronavirus [severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), previously known as 2019-nCoV], the coronavirus disease 2019 (COVID-19) was first detected in Wuhan, China. Since then, the virus has spread rapidly worldwide leading to a global public health crisis. Due to its devastating effect on public health, it is crucial to identify a viable therapeutic option to mitigate the damage the disease causes. In spite of various governments implementing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
0
32
0
3
Order By: Relevance
“…In the absence of a 2019‐nCoV‐specific pharmacological agent, various drugs have been used either singly or combined therapeutic approaches with sporadic success. Many of these drug combinations are being assessed in several of the clinical trials 28 . From among the established antivirals, remdesivir has already progressed to Phase III clinical trials (ClinicalTrials.gov Identifier: NCT04292730) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a 2019‐nCoV‐specific pharmacological agent, various drugs have been used either singly or combined therapeutic approaches with sporadic success. Many of these drug combinations are being assessed in several of the clinical trials 28 . From among the established antivirals, remdesivir has already progressed to Phase III clinical trials (ClinicalTrials.gov Identifier: NCT04292730) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Stebbing et al used AI-algorithms to identify baricitinib, an approved Janus kinase (JAK)1/JAK2 inhibitor for treating rheumatoid arthritis, to be effective at inhibiting SARS-CoV-2 infection as well as reducing virus induced inflammations ( Stebbing et al, 2020 ). Although baricitinib can cause potential adverse effect including lymphopenia, anemia and increase co-infection crisis with other pathogens ( Pujari et al, 2020 ), its combination with remdesivir is superior to remdesivir alone in improving the clinical recovery rate of patients with COVID-19 with few serious side effects ( Kalil et al, 2021 ). Ge Y. et al (2021) used machine learning and statistical analysis to uncover a ploly-ADP-ribose polymerase (PARP1) inhibitor meguparib (CVL218) which reduced SARS-CoV-2 replication without toxic effects in vitro .…”
Section: Artificial Intelligence-based Drug Discovery For Anti-sars-cov-2mentioning
confidence: 99%
“…Treating with systematic corticosteroids was a debate, but the fact that COVID-19 patients can develop a systemic in ammatory response that can lead to lung injury and multisystem organ dysfunction made this class a potential therapeutic option. 8,9 It has been proposed that the potent anti-in ammatory mechanism of corticosteroids might prevent or mitigate these deleterious effects. 10, RECOVERY trial, a multicenter, randomized, open-label trial performed in the United Kingdom, showed that a signi cant mortality reduction at 28-days in hospitalized patients who received dexamethasone for up to 10 days compared to patients who received the standard of care.…”
Section: Introductionmentioning
confidence: 99%